Primary parotid lymphoma from a regional cancer center in South India - Lakshmaiah KC; Vishwanath Sathyanarayanan; Lokesh KN; Premalatha CS; Clementina Rama Rao; Suresh TM; Govind Babu K; Lokanatha D; Linu Abraham Jacob; Umesh Das; Suresh Babu (Mediterranean Journal of Hematology and Infectious Diseases)
Background and Purpose: Primary parotid lymphoma (PPL) is an unusual entity and comprises 5% of salivary gland neoplasms and 5% of extra nodal lymphomas. There is limited data in Indian population. Hence we undertook this retrospective observational study of primary parotid lymphoma at our centre in Southern India. Results: 7 consecutive cases diagnosed as PPL by tissue biopsy/superficial/deep parotidectomy confirmed by immunohistochemistry between 2007 and 2012 were included. Median age was 54 years(29-78), and it was more common in males. Diffuse large B cell lymphoma was seen in 6 and extra nodal marginal zone lymphoma in 1. According to Ann Arbor stage- Advanced stage (stage III and IV) was seen in 2(28.57%). According to the International Prognostic Index most were in low risk- 6 (85.7%). Overall survival range from 1-45 months, with a median survival of 24 months. Conclusions: To conclude, PPL presents more often in early stage and low IPI score. Surgery with chemoimmunotherapy with involved field radiotherapy remains the standard treatment at present.